High-Resolution Secondary Reconstructions with the Use of Flat Panel CT in the Clinical Assessment of Patients with Cochlear Implants - Pearl, M.S.; Roy, A.; Limb, C.J. (American Journal of Neuroradiology, 2014)
SUMMARY: Radiologic assessment of cochlear implants can be limited because of metallic streak artifacts and the high attenuation of the temporal bones. We report on 14 patients with 18 cochlear implants (17 Med-El standard 31.5-mm arrays, 1 Med-El medium 24-mm array) who underwent flat panel CT with the use of high-resolution secondary reconstruction techniques. Flat panel CT depicted the insertion site, cochlear implant course, and all 216 individual electrode contacts. The calculated mean angular insertion depth for standard arrays was 591.9° (SD = 70.9; range, 280°). High-resolution secondary reconstructions of the initial flat panel CT dataset, by use of a manually generated field of view, Hounsfield unit kernel type, and sharp image characteristics, provided high-quality images with improved spatial resolution. Flat panel CT is a promising imaging tool for the postoperative evaluation of cochlear implant placement. CIcochlear implantEEedge enhancementFPCTflat panel CTHUHounsfield unitsMSCTmultisection CTRWround window